Pentatwinned Cu Nanowires with Ultrathin Diameters below 20 nm and Their Use as Templates for the Synthesis of Au‐Based Nanotubes. Issue 3 (24th January 2017) - Luo, Ming; Zhou, Ming; Rosa da Silva, Robson; Tao, Jing; Figueroa‐Cosme, Legna; Gilroy, Kyle D.; Peng, Hsin‐Chieh; He, Zhike; Xia, Younan
Abstract: We report a one‐pot method for the facile synthesis of Cu nanowires in high purity, together with ultrathin diameters well below 20 nm. Selected area electron diffraction and high‐resolution transmission electron microscopy studies confirm that the Cu nanowires are grown along the <110> direction to give pentatwinned, one‐dimensional nanostructures, enclosed by five {100} facets on the side surface. A systematic study further indicates that it is critical to conduct the synthesis under an argon atmosphere in order to improve the purity and uniformity of the nanowires while keeping their diameters thinner than 20 nm. We also demonstrate the use of these nanowires as sacrificial templates for the synthesis of Au‐based nanotubes through a galvanic replacement process. Abstract : When the oxygen on the two ends of Cu nanowires was removed under an argon atmosphere, the axial growth was accelerated, yielding thinner Cu nanowires (below 20 nm). In the meantime, the argon atmosphere could suppress oxidative etching, improving the yield and purity of the Cu nanowires.